Prenatal ultrasonographic diagnosis of axillary cystic hygroma - Thapa, Narayan Bikram; Dangal, Ganesh (Nepal Journal of Obstetrics and Gynaecology, 2008)
<!–[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–> <!–[if gte mso 10]> <![endif]–> Cystic hygromas are characterized by single or multiple cysts within soft tissue. They may occur in isolation or may be associated with other congenital malformations and can lead to obstructed labour or neonatal asphyxia. Ultrasonography in the prenatal period can be carried out to diagnose congenital cystic hygromas. Keywords: ultrasonography, cystic hygroma doi:10.3126/njog.v2i1.1478 N. J. Obstet. Gynaecol Vol. 2, No. 1, p. 53 - 55 May -June 2007